Online Fundraising and Social Divisions - Cyrek, Barbara; Peltonen, Jenna (POLSKIE TOWARZYSTWO SOCJOLOGICZNE-POLISH SOCIOLOGICAL ASSOC, 2025)
The global village of networked relationships implies the digitalization of community activities. An example of cultural mobilization that has recently migrated to the Internet is fundraising. Contemporary fundraising platforms enable financing usually combined with communication: asynchronous or quasi-synchronous. Supporting specific goals, individuals or groups can be a tool for building a multiplatform social identity-in particular thanks to the possibility of sharing information about fundraising and discussing them in interactive media. Digitalized financing is gaining dynamics, which can become a practice of building social divisions and fueling hatred. Against the background of Social Identity Theory, this article focuses on distortions of fundraising culture. Drawing on examples from Finland and Poland, this article takes up the characteristics of the negative dimension of fundraising.